Violence in educational institutions: A sociological analysis of its representations and manifestations within a sample of Algerian Educational Institutions - Djamel, Trik; Dahbia, Oumoussa (The International tax journal, 2026)
This sociological study aims to provide a scientific and objective diagnosis of the phenomenon of violence within educational institutions in the city of Ksar El Boukhari, by identifying the main forms of violence practiced by primary school teachers against pupils, and by uncovering the key social, cultural, and institutional factors contributing to the production and persistence of this phenomenon. The study is grounded in a sociological approach that seeks to understand the social contexts within which violent behaviour is constructed inside the school environment. To achieve the objectives of the study, a purposive sample of 265 primary school teachers was used. The study also relied on a case study method, which allowed for an in-depth analysis of the social and educational trajectories of the respondents, as well as an examination of the various experiences that have shaped their professional attitudes and practices since the beginning of their educational careers. The findings reveal that the manifestations of violence practiced by some teachers against pupils are linked to a set of social and cultural influences, primarily prevailing patterns of socialization and a reference culture imbued with values of violence and symbolic domination, which are reflected in pedagogical practices within the school.